The Influence Of Accounting Information System Utilization And Internal Control On The Quality Of Regional Financial Reports With Accounting Understanding As A Moderating Variable (Study At The Jambi Provincial Government Office) - Putra, Oky; Rahayu, Sri; Yudi, Yudi (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the impact of accounting information system utilization and internal control on the quality of local government financial reports, with accounting comprehension as a moderating variable. The research was conducted in the Provincial Government Offices of Jambi, employing a quantitative approach based on primary data collected through structured questionnaires. The sample consists of employees from 21 government offices, and data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The findings reveal that the utilization of accounting information systems does not significantly influence the quality of financial reports. In contrast, internal control has a significant positive effect. Furthermore, accounting comprehension strengthens the relationship between both accounting information systems utilization and internal control with the quality of financial reports. This study concludes that enhancing the quality of local government financial reports requires the optimization of internal controls and effective utilization of accounting information systems, supported by sufficient accounting comprehension among personnel. These insights provide valuable contributions to advancing transparency and accountability in local government financial management practices.